COLLISIONS : room for creativity and innovation in the office ; room for creativity and innovation in the office. (CUVILLIER Verlag, 2017)
What is a collision? An unexpected meeting with an effect. And what is creativity? Generating something new. And what is a creative office? It is an environment which provides support for something new. And what sounds so simple really is that simple. There are certain places in the office where creative work can really happen. These are not places like office desks or meeting rooms, no matter where they might be. Nor are these just around the coffee machines or the table-tennis tables in offices. Above all, creative places are the corridors, the lifts, the stairways, the entrance halls. In offices that have been planned with innovation in mind, it is the spaces in between that make collisions possible: chance meetings that stimulate our intuitive system and, in doing so, provide for generating something new. For intuition is a human system that enables fast decision-making and provides the means for dealing with unintended meetings that are full of risk. Coincidences are the source of the creative impulse that is needed for something new. For an idea, developing that idea, an innovation. Such locations have to be designed to support innovated exchange. Only then is an office creative. And only then will a creative meeting make an impact. Do we have such places for collisions in our offices? They are surprisingly rare.